Pengembangan Media Pembelajaran Permainan Ular Tangga Edukatif Dalam Pembelajaran Sejarah Indonesia Masa Kolonialisme Dan Imperialisme Bangsa Eropa - Satriyo Pamungkas; Ulul Azmi (Universitas Batanghari Jambi, 2021)
This study is to determine the development of educational media for playing snakes and ladders in learning the history of Indonesia during colonialism and European imperialism using the Lee and Owens model. This development model consists of five development stages, namely analysis, design, development, implementation, and evaluation. From the process of these stages, the average score at the trial stage where the product went through three stages, namely one to one (2.58) in the poor category, the small group (4.2) in the very feasible category, and the field test (4, 45) in the very category worth it. Overall from the results of these trials, the mean score was 3.74 categories (feasible).